PROMOSI KESEHATAN RISIKO DIABETES MELLITUS PADA REMAJA DI SMAN 4 SIDRAP - Masdiana; Salsabila Salsabila; Amelia Gaffar; Nur Tri Wahyuni JS; Ina Sutrisno; Fitriani Umar (Mediasi: Jurnal Pengabdian Masyarakat, 2025)
In an increasingly sophisticated and modern age, people's eating habits that prioritize convenience over health have led to an increase in non-communicable diseases such as diabetes mellitus. Diabetes mellitus is one of the most common diseases suffered by the Indonesian people, even Indonesia is ranked 7th in the world with the highest number of diabetics according to the International Diabetes Federation (IDF). Adolescents are a high-risk group because they often consume unhealthy foods without a healthy lifestyle. Based on these conditions, health promotion activities regarding the risk of diabetes mellitus were carried out at SMAN 4 Sidrap by students of the Public Health Study Program of Muhammadiyah University of Parepare. The purpose of this activity was to increase adolescents' knowledge about diabetes mellitus, including symptoms, risk factors, and preventive measures. The method used was education through lectures with PowerPoint media to 26 class XII students. The material presented included normal blood sugar levels, classic symptoms of diabetes, risk groups, and eight steps for early prevention of diabetes. The results of the activity showed an increase in participants' understanding of diabetes mellitus, which was shown by active participation during the discussion session. Health education like this is important to be carried out on an ongoing basis to foster early awareness of non-communicable diseases, especially among adolescents